2021
DOI: 10.3324/haematol.2020.270546
|View full text |Cite
|
Sign up to set email alerts
|

Red cell transfusion and alloimmunization in sickle cell disease

Abstract: Red cell transfusion remains a critical component of care for acute and chronic complications of sickle cell disease. Randomized clinical trials demonstrated the benefits of transfusion therapy for prevention of primary and secondary strokes and postoperative acute chest syndrome. Transfusion for splenic sequestration, acute chest syndrome, and acute stroke are guided by expert consensus recommendations. Despite overall improvements in blood inventory safety, adverse effects of transfusion are prevalent among … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
44
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(53 citation statements)
references
References 111 publications
0
44
0
1
Order By: Relevance
“…Classically, serum ferritin (SF) and liver biopsy have been used to monitor patients with iron overload and assess their response to chelation therapy. SF has the advantage of being widely available, but is an acute-phase reactant, and does not always correlate with body iron stores ( 33 ). MRI has now emerged as the standard of care for effective detection and quantification of iron in the heart and the liver.…”
Section: Introductionmentioning
confidence: 99%
“…Classically, serum ferritin (SF) and liver biopsy have been used to monitor patients with iron overload and assess their response to chelation therapy. SF has the advantage of being widely available, but is an acute-phase reactant, and does not always correlate with body iron stores ( 33 ). MRI has now emerged as the standard of care for effective detection and quantification of iron in the heart and the liver.…”
Section: Introductionmentioning
confidence: 99%
“…Despite overall improvements in blood inventory safety, adverse effects of BT are prevalent among SCD-patients and include RCA, acute and delayed hemolytic BT reactions. 9 BT plays a prominent role in the management of SCD-patients but causes significant iron overload. As transfusions are used to treat severe complications in SCD, it remains difficult to distinguish whether organ damage is a consequence of iron overload or is due to the complications treated by BT.…”
Section: Risk Factors Occurred Post-transfusion Complicationsmentioning
confidence: 99%
“…Early recognition and management of hemolytic transfusion reactions can avert poor clinical outcomes. 9 Identifying genetic markers may help predict which patients are at risk of forming alloantibodies. This study found 19 moderately associated SNPs, among others, SNPs in TLR1/TANK and MALT1 were associated with a higher alloimmunization risk, while SNPs in STAM/IFNAR1 and STAT4 conferred a lower alloimmunization risk.…”
Section: Risk Factors Occurred Post-transfusion Complicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Table 3 provides a summary of the characteristics of the final included studies for this review article [ 4 , 8 - 12 , 14 - 16 ].…”
Section: Introductionmentioning
confidence: 99%